APPROPRIATIZING POLITENESS THEORY FOR INTERCULTURAL COMMUNICATION IN ELT - Rahmat Yusny (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
The theory of politeness suggests strategies in social interaction by which a person can use to save the hearer’s face upon the effect of face-threatening acts or FTAs. Face threatening acts are described by Brown and Levinson as the acts that infringe the hearer’s need of maintaining his/her self-esteem and be respected. Brown and Levinson accepted that the notion of face is respected as universal norms or values subscribed to by the members of the society. In that regard, this article provides a discussion about various viewpoints on the debate of universality of politeness theory and criticisms addressed by eastern-pragmaticists that this theory should not be seen as universally applicable. Cultural differences, as suggested by non-western pragmaticists, accord what is accepted in the context of face in western culture to be not accepted in other cultures. Therefeore, although we accept that Brown & Levinson’s theory has made a significant breakthrough in elaborating politeness, appropriation of this theory should be accounted in intercultural communication instead to accept it as universal.